Dissolution of indium arsenide in nitric solutions of the hydrobromic acid - Tomashik, Z.F.; Danylenko, S.G.; Tomashik, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
Dissolution of InAs in HNO₃-HBr-H₂O solutions is studied. The surface of equal etching rates is constructed, and the limiting stages of the dissolution process are determined. Depending on the [HNO₃]/[HBr] ratio, InAs dissolution may be limited by kinetic, or diffusion, or combined mechanisms. The dissolution rate of InSb in these solutions is rather low, and the etched surface is covered with a friable sediment. HNO₃ -HBr-H₂O solutions can be employed for a dynamic chemical polishing of InAs with a variable etching rate.